Development of Land Legal Policy in The Reform Era Reviewed from The Perspective of Agrarian Justice - Muhammad Farrel Haristyanto; Moh. Indra Bangsawan; Clarizze Yvoine Mirielle (Universitas Muhammadiyah Surakarta, 2023)
Law Number 5 of 1960 concerning Basic Land Regulations or what we know as the Basic Land Law (UUPA) is one of the general policies in the form of statutory regulations that have been implemented for approximately 48 years. Land policy in Indonesia viewed from the perspective of agrarian justice is still not appropriate because in all social, political, legal and economic institutions, justice is the basic structure of society; because the regulation of social institutions has a fundamental impact on the prospects of an individual's life, the implementation of the UUPA has undergone various changes due to differences in the sequence of visions, missions, strategies, policies and government programs. Seeing that the human values embedded in land legislation are decreasing. The need for reform in the field of land law continues to emerge and continues to be carried out by the community, but the government has so far maintained the legitimacy of the UUPA by trying to adapt to the conditions that are developing in the current reform. This study aims to find out how land law policies in Indonesia and how land law policies are viewed from the perspective of agrarian justice. Then these problems are examined using descriptive-qualitative research methods using descriptive research types and secondary data sources.